STRATEGI PENGEMBANGAN KAPASITAS PRODUKSI UMKM SEKTOR MAKANAN DAN MINUMAN DI KOTA SERANG - Mukhlis, Ahmad; Khaeruman, Khaeruman; Suflani, Suflani; Lesmana, Ihwan Satria (Yayasan Education and Social Center, 2024)
This research aims to identify effective strategies in developing the production capacity of MSMEs in the food and beverage sector in Serang City. MSMEs in this sector face major challenges in the form of limited traditional production technology and low human resource skills in production management and quality control. This research uses qualitative and quantitative approaches using in-depth interviews, field observations and surveys. The research results show that key strategies that can be implemented include the application of modern and efficient production technology, increasing human resource skills through training and mentoring, as well as increasing access to capital and local government support. The implementation of this strategy is expected to increase productivity, efficiency, product quality consistency and the competitiveness of MSMEs in the food and beverage sector in Serang City. The findings of this research provide an important contribution to the development of MSMEs and the local economy in Serang City